THE APPLICATION OF FRIEND’S STORY TECHNIQUES TO IMPROVE THE NARRATIVE WRITING SKILLS OF STUDENTS OF MTSN 4 ACEH BARAT - Husaini, Husaini; Hayati, Cut Intan; Wardiana, Wardiana (LUMBUNG AKSARA, 2022)
The purpose of this study was to improve teacher’s skills in writing narrative essays in class VII of MTsN 4 West Aceh. The design of this study used classroom action research with the stages of planning, implementing, observing, and reflecting. The research subjects were teachers and students of class VII of MTsN 4 West Aceh. The data collection techniques used were tests, documentation, observations, and field notes. This research used qualitative and quantitative data analysis. The results showed that there was an improvement in teacher’s skills, students’ activity, and narrative essay writing skills. Teacher’s skills in cycle I was 81.25% with good criteria (B) and it increased into 97% in cycle II with very good criteria (A). Students’ activity in cycle I was 69% with good criteria (B) and it reached 89% in cycle II with very good criteria (A). The Completeness of students’ learning outcomes in cycle I was 78.37%, and it reached 100% in cycle II.